Pengaruh Return on Assets, Return on Equity, Earning per Share terhadap Harga Saham (Studi Kasus pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2018-2020) - Merida (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: This study aims to determine the effect of Return on Assets, Return on Equity, Earning Per Share on share prices in mining companies listed on the IDX in 2018 - 2020. Background Problems: The number of business competitors results in business dynamics that are constantly changing so that many companies need additional funding to further develop their business so that they are able to survive. Novelty: Re-examining the factors used by previous studies which yielded contradictory results. Research Methods: The method used to take samples is non-probability sampling using purposive sampling method with the EViewss data processing application. Finding/Results: Purchasing shares in the mining sector or company should consider the RoA, RoE and EPS factors because these factors have long-term and short-term effects on stock prices. Conclusion: Return on Assets and Earning Per Share have a significant effect on stock prices, but Return on Equity has no effect on shares in mining sector companies listed on the IDX.